Heritability of major depressive and comorbid anxiety disorders in multi‐generational families at high risk for depression. Issue 8 (25th July 2016) - Guffanti, Guia; Gameroff, Marc J.; Warner, Virginia; Talati, Ardesheer; Glatt, Charles E.; Wickramaratne, Priya; Weissman, Myrna M.
Abstract : Family studies have shown that MDD is highly transmittable but have not studied its heritability. Twin studies show heritability of about 40% and do not include anxiety disorders. We assessed heritability of MDD and comorbid anxiety disorders in a multigenerational study of family members at high risk for MDD. In addition, we tested the hypothesis that examined clinical subtypes of MDD defined by early and late age of onset would be under relatively stronger genetic control than broadly defined DSM‐IV MDD. The first generation with moderate to severe MDD was recruited from an ambulatory psychiatric treatment setting, and their descendants in the second, third, and fourth generation, were interviewed by clinicians up to six times during a 30‐year period. Lifetime rates of MDD and anxiety disorders were collected for 545 participants from 65 multigenerational families. The heritability (h 2 ) of MDD in this high risk sample was estimated at 67%. Anxiety and sequential comorbidity of anxiety disorders and MDD revealed h 2 of 49% and 53%, respectively, and strong positive genetic correlation (rhog  = 0.92, P  = 7.3 × 10 −7 ). Early onset MDD did not appear to be under greater genetic control than broadly defined DSM‐IV MDD. Individuals who are direct descendants of subjects ascertained for moderate to severe MDD have strong genetic vulnerability to develop anxiety or MDD. Our findings support family based studies as appropriate and useful design to understand the heritability of common disorders such as MDD. © 2016 Wiley Periodicals, Inc.